PENGARUH METODE PEMBELAJARAN PROYEK TERHADAP KEMAMPUAN SOSIAL ANAK USIA 5-6 TAHUN (Penelitian Kuantitatif Survei di Kecamatan Serang Kota Serang Banten) - Ananda, Fitria Sri; Rusdiyani, Isti; Khosiah, Siti (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2021)
Social ability is the ability to communicate, interact, the ability to be able to show good behavior and the ability to establish good relationships with other people or the community around them so that they can behave in accordance with what is expected by the social. This study aims to determine the effect of project learning methods on the social skills of children aged 5-6 years. This research was conducted on teachers who were in the sub-district of Serang, Kota Serang, Banten. The method used in this research is survey research by distributing questionnaires to schools in Serang sub-district and has implemented project learning methods with a sample of 30 teachers. The results showed that the correlation coefficient of project learning methods on the social abilities of children aged 5-6 years showed a number of 0.622 which means that it has a strong influence. So it can be concluded that there is a significant effect of using project learning methods on the social abilities of children aged 5-6 years.